2018
DOI: 10.1111/1556-4029.13806
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of the Trotter Tibia Quandary and its Continued Effect on Stature Estimation of Past‐Conflict Service Members

Abstract: Forensic casework from past-conflicts relies on the corrected historical Trotter data for stature estimation in Fordisc. For roughly 10 years', stature estimation using this data has produced point estimates for the tibia that are on average 1.25 inches less than the other long bones. This issue was identified after applying the equations derived from Fordisc to the USS Oklahoma commingled assemblage. Reevaluation of Fordisc revealed that a correction factor of 20 mm, instead of 10 mm, was mistakenly applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
11
1
Order By: Relevance
“…That both ordinary length and "maximum length" were longer than WW2 core suggests that the former was measured as Trotter measured "maximum length", and "maximum length" was actually condylar-malleolar length, perhaps guided by Trotter's actual definition. This small series offers support for Lynch et al's (6) suggestion that some WW2 were measured to include the malleolus, but it has no bearing on stature estimation because there is no evidence it was ever used for that. During the course of this investigation, additional errors were discovered.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…That both ordinary length and "maximum length" were longer than WW2 core suggests that the former was measured as Trotter measured "maximum length", and "maximum length" was actually condylar-malleolar length, perhaps guided by Trotter's actual definition. This small series offers support for Lynch et al's (6) suggestion that some WW2 were measured to include the malleolus, but it has no bearing on stature estimation because there is no evidence it was ever used for that. During the course of this investigation, additional errors were discovered.…”
Section: Discussionmentioning
confidence: 52%
“…They found that the 10 mm adjustment in Jantz et al (2) produced height estimates systematically different when compared to other bones, and that an adjustment of 6 mm was more appropriate. Lynch et al (6) concluded this difference may be attributable either to a difference between how Trotter measured the Terry collection or to how the World War 2 (WW2) tibiae were measured. They suggest two possibilities.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the current sample's Tib with those of Trotter and Gleser did not differ significantly (One sample t ‐test; p = 0.583 and p = 0.504 for the left and right Tib, respectively). This result was not affected by the 6 mm correction factor applied to the Trotter and Gleser's tibia length (One sample t ‐test; p = 0.176 and p = 0.204 for the left and right Tib, respectively). Therefore, it was concluded that no significant size discrepancies exist between the samples of this study and Korean War casualties.…”
Section: Discussionmentioning
confidence: 85%